PSIX-13 Influence of herbage allowance and beef cow genotype on herbage intake during mid-gestation in Campos grassland. (5th December 2019) - Carmo, Martin Do; Genro, Cristina; Cibils, Andres; Soca, Pablo
Abstract: The objective of this study was to measure herbage intake rate (g/kgBW0.75/d) of purebred (Pu, Hereford/Angus) and crossbred (Cr, F1 of Hereford/Angus) beef cows grazing under high (Hi) and low (Lo) annual herbage allowance (HA, mean 5 vs 3 kgDM/kgBW) but equal winter herbage allowance (3 kgDM/kgBW). Herbage intake was measured in 32 gestating cows (from -96 to -76 and -92 to -77 days to calving in y1 and y2 respectively) via n-alkanes C32. Cows were placed in one of 8 groups within 2 blocks (each block four paddocks) of HA x cow genotype treatment. In mid-gestation average herbage mass (±SE) was Hi = 1410 vs Lo = 710 ±230 kg DM/ha (P < 0.05) in y1, and Hi = 850 vs Lo = 570 ±230 kg DM/ha (P = 0.38) in y2. Cow genotype did not affect herbage mass, and CP (8.6±0.37%) and ADF (40.6±1.2%) concentration were not affected by HA. Cow BW (kg±SE) in Hi vs. Lo HA was 478 vs 452 ± 20(P = 0.35) for y1 and 456 vs 393 ± 17(P < 0.05) for y2, while cow BW in Cr vs Pu was 477 vs 453 ± 17 (P = 0.34) and 448 vs 407 ± 17 (P = 0.09) for y1 and y2, respectively. Herbage allowance affected herbage intake (g/kgBW0.75/d) in y2, Hi = 77 vs Lo = 70 ±0.3 (P < 0.05) but not in y1 (Hi = 103 vs Lo = 97 ±0.3, P = 0.19) while Cr cows had lower herbage intake Pu = 108 vs Cr = 92 ±0.3 Cr (P < 0.05) and Pu = 79 vs Cr = 68 ±0.3 (P < 0.05) y1 and y2, respectively. Intake rates were affected by HA and animal genotype. High HA increased intake rates 10% and Cr cows decreased 17% herbage intake rate. Our results provide mechanistic criteria to manage stocking rates on Campos cattle ranches.